Small-scale in vitro culture and purification of Plasmodium berghei for transfection experiment - Somsak V. (2014)
The standard protocol for genetic modification of the rodent malaria parasite Plasmodium berghei requires infected blood from one or more laboratory mice, followed by large-scale in vitro parasite culture and purification of mature schizonts. Here, protocols are described for small-scale in vitro culture from 20 μL of mouse tail blood and purification of mature P. berghei schizonts sufficient for a single transfection experiment. All procedures are performed in 1.5-mL microcentrifuge tubes. We confirmed that transgenic parasites could be obtained using schizonts prepared by this protocol. This small-scale protocol provides significant advantages, namely reduction of parasite sample, laboratory consumables and mice for transfection experiments. © 2011 Elsevier B.V. All rights reserved.